2019
DOI: 10.1038/s41393-019-0254-8
|View full text |Cite
|
Sign up to set email alerts
|

Accuracy of the Actigraph wGT3x-BT for step counting during inpatient spinal cord rehabilitation

Abstract: Study design Cross-sectional. Objectives (1) Assess the accuracy of the Actigraph wGT3x-BT accelerometer to count steps taken by inpatients with incomplete spinal cord injury (iSCI) in physical therapy (PT) sessions and self-directed activities, and (2) compare the number of steps/min taken in PT sessions to that in self-directed activities during inpatient rehabilitation. Setting Inpatient spinal cord injury rehabilitation. Methods Seventeen individuals with subacute motor iSCI were observed for up to 45-min … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 26 publications
0
4
0
Order By: Relevance
“…The AG is not a true criterion measure on PA outputs in a free living context and varying results have been found when testing the validity of AG against e.g. manual counted steps [34,[59][60][61]. For EE, doubly labeled water is considered the gold standard [62] and for measuring steps, it has been suggested that the StepWatch [63,64] is the most accurate while some have attempted the use of video-recording [65].…”
Section: Plos Onementioning
confidence: 99%
“…The AG is not a true criterion measure on PA outputs in a free living context and varying results have been found when testing the validity of AG against e.g. manual counted steps [34,[59][60][61]. For EE, doubly labeled water is considered the gold standard [62] and for measuring steps, it has been suggested that the StepWatch [63,64] is the most accurate while some have attempted the use of video-recording [65].…”
Section: Plos Onementioning
confidence: 99%
“…Among these devices, ActiGraph is one of the most commonly used activity monitors for research in various populations [ 12 , 13 ]. ActiGraph is used to quantify the volume of walking (e.g., step count and distance) in people with incomplete spinal cord injury [ 14 ], hospitalized elderly [ 15 , 16 ], stroke survivors [ 17 19 ], children aged 10–17 years [ 20 , 21 ], people with multiple sclerosis [ 22 , 23 ], or in healthy people [ 24 27 ]. There are several models of ActiGraph that, vary according to type of sensors (e.g., accelerometer, gyroscope) and data processing (e.g., filter).…”
Section: Introductionmentioning
confidence: 99%
“…Since it is designed to be worn on the wrist, error of the vivofit3 on the ankle (VA) can be explained by its placement and, therefore, not recommended; however, error of the Link on the wrist and ankle (LW and LA, respectively) is more difficult to interpret since previous studies have found it to be accurate [67,68], while others found it to have a greater degree of error at various speeds [66,69]. Differences in findings may be explained by the placement of the device, surface on which participants walk (over ground or treadmill), sampling rate used (for example, 100 Hz as opposed to 50 Hz), population used (healthy, neurological disorder, elderly, etc.…”
Section: Discussionmentioning
confidence: 99%